Acute Cellular and Antibody‐Mediated Rejection of the Pancreas Allograft: Incidence, Risk Factors and Outcomes. Issue 11 (19th September 2013) - Niederhaus, S. V.; Leverson, G. E.; Lorentzen, D. F.; Robillard, D. J.; Sollinger, H. W.; Pirsch, J. D.; Torrealba, J. R.; Odorico, J. S.
Abstract : Antibody‐mediated rejection (AMR) after pancreas transplantation is a recently identified entity. We describe the incidence of, risk factors for, and outcomes after AMR, and the correlation of C4d immunostaining and donor‐specific antibody (DSA) in the diagnosis of AMR. We retrospectively analyzed 162 pancreas transplants in 159 patients who underwent 94 pancreas allograft biopsies between 2006 and 2009. Univariate and multivariate analyses were performed to evaluate risk factors for pancreas graft AMR. One‐year rejection rates and survival after rejection were calculated by Kaplan–Meier methods. AMR occurred in 10% of patients by 1‐year posttransplant. Multivariate risk factors identified for AMR include nonprimary simultaneous pancreas–kidney (SPK) transplant, primary solitary pancreas (PAN) transplant and race mismatch. After pancreas rejection, patient survival was 100% but 20% (8 of 41) of pancreas grafts failed within 1 year. Graft survival after acute cellular rejection (ACR), AMR and mixed rejection was similar. Of biopsies that stained >5% C4d, 80% were associated with increased Class I DSA. In summary, AMR occurs at a measurable rate after pancreas transplantation, and the diagnosis should be actively sought using C4d staining and DSA levels in patients with graft dysfunction, especially after nonprimary SPK and primary PAN transplantation. Abstract : This study of "for‐cause" pancreas allograft biopsies in transplant recipients demonstrates that antibodymediated rejection occurs in approximately 10% of patients in the first year with associated risk factors including retransplantation, solitary pancreas transplantation and donor‐recipient race mismatch.